Pencegahan Fraud Dana Desa: Analisis Ketaatan Aturan Akuntansi dan Sistem Pengendalian Intern - Sinen, Kasim (Insan Cita Bongaya Research Journal, 2022)
The purpose of the study was to examine the effect of compliance with accounting rules and internal control systems on the prevention of village fund fraud. Respondents in this study were village officials in the district of Central Adonara, East Flores Regency, totaling 65 village officials. Source of data is primary data multiple linear regression analysis method. The results of the study show that compliance with accounting rules has no significant effect on preventing village fund fraud. While the internal control system has a significant positive effect on preventing village fund fraud.